Imaging the kidney using magnetic resonance techniques: structure to function. Issue 6 (November 2016) - Mahmoud, Huda; Buchanan, Charlotte; Francis, Susan T.; Selby, Nicholas M.
Abstract : Purpose of review: MRI can noninvasively assess the structure and function of the kidney in a single MRI scan session. This review summarizes recent advancements in functional renal MRI techniques, with a particular focus on clinical applications. Recent findings: A number of MRI techniques now provide measures of relevance to the pathophysiology of kidney disease. Diffusion-weighted imaging, used in chronic kidney disease and renal transplantation, shows promise as a measure of renal fibrosis. Longitudinal relaxation time (T1 ) mapping has been utilized in cardiac MRI to measure fibrosis and oedema; recent work shows its potential in the kidney. Blood oxygen-level-dependent MRI to measure renal oxygenation has been extensively studied, but a number of other factors affect results making it hard to draw definite conclusions as to its utility as an independent measure. Phase contrast and arterial spin labelling can measure renal artery blood flow and renal perfusion without exogenous contrast, as opposed to dynamic contrast-enhanced studies. In general, current data on clinical use of functional renal MRI are restricted to cross-sectional studies. Summary: Renal MRI has seen significant recent advances. Current evidence demonstrates its potential, and next steps include wider evaluation of its clinical application.